Infant mortality trend in the city of Rio Branco, AC, 1999 to 2015 - Ramalho, Alanderson Alves; Andrade, Andréia Moreira de; Martins, Fernanda Andrade; Koifman, Rosalina Jorge (Revista de Saúde Pública, 2018)
OBJECTIVE: Analyze the trend of infant mortality in Rio Branco, state of Acre, from 1999 to 2015. METHODS: An ecological observational study of a time series, in which data from deaths from the Information System on Mortality and Births of the Information System on Live Births were used. The annual percentage change was estimated using the Joinpoint software. RESULTS: The infant mortality rate decreased from 26.99 in 1999 to 14.50 in 2015 per 1,000 live births, with an annual percentage change of -4.37 (95%CI -5.4– -3.4). When stratified by age components, the neonatal period presented an annual percentage change of -4.73 (95%CI -5.7– -3.7), and the post-neonatal period was -3.7 (95%CI -5.4– -2.0). Avoidability, avoidable causes and poorly defined causes showed a downward trend throughout the period and causes not clearly preventable showed an upward trend until 2008. The group of causes that contributed most to the infant deaths during the period studied was perinatal diseases, followed by malformations, infectious and parasitic diseases, and respiratory diseases. CONCLUSIONS: Despite the decreasing trend in infant mortality rates in the capital compared to developed countries, it is relatively high.